Myocardial depression in a calf with septic shock. Issue 1 (26th February 2018) - Naseri, Amir; Turgut, Kursad; Sen, Ismail; Ider, Merve; Akar, Aybars
Abstract : A 10‐day‐old, 32‐kg Simmental heifer calf was presented with a 2‐day history of diarrhoea and anorexia. The diagnosis of septic shock was based on the presence of severe sepsis and hypotension that could not be reversed with fluid resuscitation. Echocardiographic findings included a hypokinetic left ventricle with decreased left ventricle ejection fraction, stroke volume and cardiac index. The end‐systolic volume index (ESVI) was elevated to 36.14 ml/m 2 and a depressed end‐diastolic volume index (EDVI) (51.31 ml/m 2 ). Left ventricular depression was normalised 24 hours after resuscitation. It was concluded that myocardial depression could be reversible in the calf with septic shock; however, according to the postresuscitation echocardiographic findings, a decreased ESVI suggests vasomotor dysregulation and a decreased EDVI suggests alterations in vascular permeability. These were the major implications of sepsis and resulted in multiple organ dysfunction and death.